2018
DOI: 10.1136/heartjnl-2017-312850
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal change in blood pressure is associated with cardiovascular disease mortality in a Chinese cohort

Abstract: Background A number of studies have demonstrated a J-shaped curve between blood pressure and all-cause mortality, but few studies have used longitudinal change in blood pressure to study mortality in the Chinese population. Methods We performed a 30-year follow-up study to examine the association between blood pressure (at baseline and longitudinal change) and risk of mortality in the Linxian General Population Trial Cohort. At baseline, a total of 29,584 healthy adults were enrolled in the Linxian General P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 31 publications
0
30
1
Order By: Relevance
“…A pooled analysis of seven cohorts from Norway, Austria and Sweden has suggested a higher risk of cancer mortality with the elevated BP 25. However, there is little support for hypertension and cancer incidence risk in a Swedish Trial of old patients22 and a recent Chinese study from the Linxian Nutrition Intervention Trial 12. Several mechanisms may explain the inverse associations observed for cancer in our study.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…A pooled analysis of seven cohorts from Norway, Austria and Sweden has suggested a higher risk of cancer mortality with the elevated BP 25. However, there is little support for hypertension and cancer incidence risk in a Swedish Trial of old patients22 and a recent Chinese study from the Linxian Nutrition Intervention Trial 12. Several mechanisms may explain the inverse associations observed for cancer in our study.…”
Section: Discussioncontrasting
confidence: 51%
“…BP change over time may have greater power in predicting total and cardiovascular mortality. Limited studies in China have examined the potential effect of change in BP 12. In our study, we included subjects with at least two measurements of BP to examine the potential effect of BP change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have confirmed and reinforced the importance of BP change by different forms for stroke. Limited prospective studies in the form of longitudinal elevated or decreased BP trajectories at several time points have emphasized that increase in BP is a major risk factor for adverse outcomes of CVD (including stroke) in China or Western countries . Another form of BP changes is the visit‐to‐visit blood pressure variability, and studies have found that higher variability of BP or SBP is a powerful predictor of cardiovascular events independently of mean SBP or DBP, which has been more common in previous studies .…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic BP changes include more critical information for prediction of stroke risk, having higher accuracy and sensitivity . Several lines of evidence that visit‐to‐visit variability (VVV) of BP or trajectory changes in BP are associated with a higher incidence of CVD and a higher risk of mortality . However, few studies have concentrated on the effects of BP changes on stroke and its subtypes, and most of those studies were conducted either in Western countries or focused on the adverse outcomes affected by BP changes during the same time period or same multiple time periods .…”
Section: Introductionmentioning
confidence: 99%